PERBEDAAN INFORMASI CITRA DIAGNOSTIK ANTARA SEKUEN T2 TSE STIR DAN T2 TSE DIXON PADA PEMERIKSAAN MRI LUMBAL POTONGAN SAGITAL DENGAN KASUS RADICULOPATHY - Fisnandya Meita Astari; Rasyid; Fatimah (Perhimpunan Radiografer Indonesia (PARI), 2018)
Backgroud: T2 Weighted Image Turbo Spin Echo Short Tau Inversion Recovery (T2 TSE STIR) is a sequence to get the image pathologic which can reveal of tissue along surrounding pathology with fat suppresion technique. T2 Weighted Image Turbo Spin Echo Dixon is a sequence to get the image pathologic whic can reveal of tissue along surrounding pathology with fat and water suppresion technique. Based on observations at Dr. Hasan Sadikin Bandung Hospital, in the examination of MRI Lumbal using T2 TSE sequence with Dixon fat suppresion technique, while according to The American College of Radiology (2012), using STIR fat suppresion technique. The purpose of this research was to know the difference of information diagnostic image that is produced between T2 TSE STIR and T2 TSE Dixon sequences on the examination of MRI lumbal sagittal slice with Radiculopathy case. Methods: This research of type is experiment. The study was conducted with a 1,5 Tesla MRI at Installation Radiology of General Hospital Dr. Hasan Sadikin Bandung. The research took from of the 22 images of MRI lumbal sagittal slice from T2 TSE STIR and T2 TSE Dixon sequences with Radiculopathy cases. Assesment of the image was done by two respondents and Kappa test was conducted. Furthermore, the results of respondents assessment was analyzed by Wilcoxon different test. Results: The results showed that the research result Ho rejected and Ha accepted which mean there is a differences of information diagnostic image between T2 TSE STIR and T2 TSE Dixon sequences on the examination of MRI lumbal sagittal slices with Radiculopathy case with p value = 0,001 (p <0,05). Conclusion: T2 Sequence TSE Dixon can produce MRI images with more specific and homogeneous fat suppresion, thus providing more informative diagnostic information than T2 TSE STIR sequences.